2019
DOI: 10.1515/epoly-2019-0029
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of rosin-based polymer microspheres as a stationary phase in high-performance liquid chromatography to separate polycyclic aromatic hydrocarbons and alkaloids

Abstract: Acrylpimaric acid ethylene glycol acrylate was used as the cross-linking agent to prepare rosin-based polymer microspheres through membrane emulsification–microsuspension polymerization. The prepared microspheres were used as the stationary phase in high-performance liquid chromatography for the separation of polycyclic aromatic hydrocarbons (PAHs) and two analogues of alkaloids. Five PAHs (benzene, naphthalene, fluorene, pyrene, and benzo(e)pyrene) were well separated in the rosin-based polymer column with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Rosin developed by Wang et al showed a good ability to separate PAHs. Rosin was synthesized by a monomer methyl methacrylate and ethylene glycol dimethacrylate, a crosslinker acryl pimaric acid ethylene glycol acrylate, and an AIBN catalyst [ 107 ]. Peng et al also succeeded in synthesizing a capillary column from the polymerization reaction of 12-methacryloyl dodecylphosphatidic acid and ethylene glycol dimethacrylate with an AIBN catalyst [ 45 ].…”
Section: Development Of Stationary Phases For Pahs Capturementioning
confidence: 99%
“…Rosin developed by Wang et al showed a good ability to separate PAHs. Rosin was synthesized by a monomer methyl methacrylate and ethylene glycol dimethacrylate, a crosslinker acryl pimaric acid ethylene glycol acrylate, and an AIBN catalyst [ 107 ]. Peng et al also succeeded in synthesizing a capillary column from the polymerization reaction of 12-methacryloyl dodecylphosphatidic acid and ethylene glycol dimethacrylate with an AIBN catalyst [ 45 ].…”
Section: Development Of Stationary Phases For Pahs Capturementioning
confidence: 99%
“…One of the most important actual challenges in designing these combined systems is how to keep or increase the best properties of each component while rejecting or decreasing their limitations [ 6 ]. Organic-inorganic materials based on a polymer matrix are some of the most frequently obtained types of hybrid systems because of their ease of synthesis and further modification [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polymer‐based microspheres have gained importance in a broad range of fields during the last decade since they can be widely used in several industrial sectors such as chromatography separation, biomedical devices, coating additives, and controlled release reservoirs 1–3 . Polymer‐based microspheres present a spherical geometrical shape and can be manufactured to have a uniform size that ranges from nanometer to micrometer scale 1,2 .…”
Section: Introductionmentioning
confidence: 99%